Removal of cationic dyes by adsorption in a single and binary system using activated carbon prepared from the binary mixture - Kilic, Aysegul; Orhan, Ramazan (Taylor & Francis Inc, 2019)
An activated carbon (AC) was developed from a mixture of almond and apricot stone shell with a sufficient source of raw material to investigate its ability to remove BY51 and BB3 dyes from aqueous solutions. It was found that the adsorption of BY51 (657.89 mg/g) and BB3 (588.24 mg/g) dyes in a single system can be better described with Langmuir isotherm according to the R-2 values. Equilibrium uptake of BY51 and BB3 in binary mixture onto AC declined with a rise in concentrations of the other dye due to their antagonistic behavior. ELE and JSME models were employed to determine the isotherm data for the binary systems. BY51 and BB3 adsorption kinetics were also analyzed in single and binary systems.
Keywords: Activated carbon; adsorption; binary mixture; cationic dye